EGG AND SPERM STRUCTURE OFTHE BAGRID CATFISH, Mystus nemurus - Muchlisin Z. A. (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2004)
Egg and sperm structure of bagrid catfish, Mystus nemurus were observed using transmission (TEM) and scanning electron microscopy (SEM). The objective of the present was to evaluate structure of the egg and spermatozoa of bagrid catfish. The egg samples were preserved in a 10% formaldehyde and 1% gluteraldehyde fixative and dehydrated by a series of ethanol. Then after, the egg samples were soaked in xylene and wax then embedded and sliced by a microtome, stained and observed by a light microscope. Sperm samples were fixed in 2.5% McDowell-trump fixative and post fixed in cacodylate buffer osmium tetroxide. For SEM the samples were attached to cover slip previously coated with 0.1% poly-L-lysin and dehydrated by a series of acetone then critical point dried and coated with gold. While, for TEM the pellet samples obtained by gentle centrifugation were dehydrated in acetone and embedded in resin. Tliin sections of samples were picked up on copper grids, doubly stained with uranyl acetate and lead citrate. The results showed that normal spermatozoa of bagrid catfish consist of three distinct parts; head, midpieces-sleeve, and uninagellate of flagellum with nine peripheral doublets and single pair of central microtubulus (“9+2” patterns) of axoneme. The egg is oval and divided into three layers and can be classified as a non buoyant. Many micropores and single microphyle were detected on surface of the egg.